Empowerment Tourism Village Natural Resources in Improving the Economy of the Community of Pagar Alam City, South Sumatera Province - Juniarni, Cittra; Rohani, Tri; Nuryani; Almujahid; Nuraini, Sinta (Research and Social Study Institute, 2022)
Natural resources are something that can be used for various interests and needs of human life in order to live a more prosperous life around our natural environment. Utilization of a resource is determined based on the use of these resources for humans themselves. Therefore, the more useful a natural resource is, the more valuable it will be. Utilizing existing natural resources is a form of empowerment based on local potentials that strongly supports community development. Good natural resources management can improve the welfare of local communities. The implementation of community service activities (PKM) was carried out by using the Focus Group Discussion (FGD) method and the approach method with related parties, especially the Pagar Alam City Tourism Office. In addition, the collection of data on the potentials and natural resources in Pagar Alam is also carried out through a database search at the Tourism Office. From the results of the data collection obtained, it can be concluded that the empowerment of natural resources in Pagar Alam City can help the community's economic growth. Based on data from the Central Bureau of Statistics of Pagar Alam City, Pagar Alam City's economic growth in 2021 grew by 4.39%. The highest growth was achieved by the accommodation and food and drink provision sectors at 8.83%. This is an indication of the empowerment of existing natural resources. Pagar Alam with its potentials can be further developed into an international standard tourist village by implementing the empowerments given.